Beyond Woodhouse: Devising New Principles for Determining ACC Boundary Issues - Oliphant, Ken (Victoria University of Wellington Law Review, 2004)
This paper argues that there is a need to identify new, midlevel principles that provide guidance as to how to draw the boundaries of ACC for as long as it remains a scheme of limited scope. The Woodhouse principles are not suited to this task as they point towards a universal scheme, embracing both injury and illness. The author believes that it is necessary to adopt a principled approach to what is included in ACC and what is left outside. The paper concludes by suggesting that these new principles should be based on a consideration of the nature of the dual public/private responsibility for incapacity and that where the question, "is it legitimate to leave this category of incapacity to the private sphere?" is answered negatively, there is a case for extending the scope of ACC coverage, even if this means transgressing the boundary between injury and illness.